A importância da utilização do jogo didático para o ensino de matemática no 7o ano do ensino fundamental - Barreto, Igor José Teles (2020)
The aversion to the discipline of mathematics is something historical and still recurring today, as this is not one of the subjects that students like most and are interested in learning. Bearing in mind that the use of the didactic game in the teaching of mathematics can lead the student to a process of acquiring essential information for his cognitive, emotional and social development through playfulness, we decided then to apply a didactic game with the purpose of making with the students to like mathematics and to see it with a different look, in a meaningful way for their lives and more dynamic. Thus, the main interest in this work is to analyze the potential of the game as a didactic tool for teaching mathematics, based on the opinions of students, as well as to identify the importance of using games as a didactic tool for teaching mathematics and know the students' knowledge about these didactic tools for teaching. To this end, a research was carried out with 14 students from the 7th year, who participated in the online application of the game Bingo ZOCNI with the following theme: Set of Integer Numbers-operations with integers (addition, subtraction, multiplication, division and potentiation). Then, a questionnaire was applied through Google forms that included the questioning of the research. Thus, the research is characterized as an exploratory research with a qualitative and quantitative approach. Data analysis was carried out in an analytical-interpretative manner, which allowed us to conclude that didactic games arouse students' interest in mathematics and the content covered. In addition, it was noticed that the use of these materials is common in mathematics classes, since 100% of the students stated that they have already participated in games in this discipline. We also concluded that these materials contribute to the understanding and understanding of the contents, during mathematics classes and have numerous advantages such as arousing interest, drawing attention and arousing students' curiosity. It was also possible to conclude that these materials make the class more attractive, dynamic, fun, pleasant and interesting, thus enabling the association of learning with playfulness.